Pseira X : the excavation of Block AF - Betancourt, Philip P. (Prehistory monographs, 2009)
"This book is the tenth volume in the series of excavation reports about the harbor town of Pseira, which is located on the island of the same name, just off the northeast coast of Crete. The book focuses on the excavation and interpretation of the architecture and material culture in Block AF. This southern group of buildings is one of the most important areas in the settlement because of its long succession of building phases. Block AF provides the fullest sequence of building phases from any one area at Pseira, with habitation extending from before MM II to LM III. It has examples of complex architectural details including a "pillar crypt," elaborate upstairs floors, a well-preserved U-shaped staircase, and a well-designed kitchen, all of which contribute significantly to our knowledge of East Cretan building practices. In addition to domestic pottery, the houses furnish examples of stone tools, stone vessels, loom weights, inscriptions in Linear A, cult objects, animal bones, marine shells, and a wide range of material recovered from water sieving. This latter category, with burned grain, fish bones, shells, and other categories of materials, fills many gaps in our knowledge of Pseiran life."--Publisher's website